2015
DOI: 10.1021/es503676p
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemical Oxidants on Perfluoroalkyl Acid Transport in One-Dimensional Porous Media Columns

Abstract: In situ chemical oxidation (ISCO) is a remediation approach that is often used to remediate soil and groundwater contaminated with fuels and chlorinated solvents. At many aqueous film-forming foam-impacted sites, perfluoroalkyl acids (PFAAs) can also be present at concentrations warranting concern. Laboratory experiments were completed using flow-through one-dimensional columns to improve our understanding of how ISCO (i.e., activated persulfate, permanganate, or catalyzed hydrogen peroxide) could affect the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 34 publications
0
50
0
Order By: Relevance
“…Few studies to date have investigated the affect of ISCO treatment on subsurface mobility of PFASs. One research group observed decreased PFAA transport in column studies with persulfate treatment at room temperature, 50 but further research is needed to assess the impact of persulfate treatment on transport of polyfluorinated compounds under heat-activation conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies to date have investigated the affect of ISCO treatment on subsurface mobility of PFASs. One research group observed decreased PFAA transport in column studies with persulfate treatment at room temperature, 50 but further research is needed to assess the impact of persulfate treatment on transport of polyfluorinated compounds under heat-activation conditions.…”
Section: Resultsmentioning
confidence: 99%
“…This “molecular brush” mechanism of surface interaction may also prove to be relevant in fate and transport of PFASs in the environment. For PFAAs, sorption typically increases with decreasing pH and increasing concentration of calcium (Ca 2+ ; ionic strength; Higgins & Luthy, ; McKenzie, Siegrist, McCray, & Higgins, ). At increasing ionic strengths the authors have observed a diminished ratio of straight chains to branched chain PFOS, which may be accounted for by the “molecular brush” sorption mechanism described earlier.…”
Section: Overview Of Pfas Environmental Chemistrymentioning
confidence: 99%
“…Lower pH has also been shown to increase sorption, as has substituting calcium for sodium in solution for anionic PFAS, suggesting that while organic carbon effects dominated sorption to soil, ionic effects are also significant (Higgins & Luthy, ). A study on the impact of remediation oxidizers ( in situ chemical oxidation) on PFCA mobility found that the oxidizers had little impact on the PFCAs, but did greatly impact mobility, with permanganate and peroxide increasing transport and persulfate reducing transport (McKenzie, Siegrist, McCray, & Higgins, , ). It was thought that especially permanganate, but also peroxide, liberated soil organic matter and increased the mobility of the PFAAs, while persulfate had little impact on soil organic matter.…”
Section: Behavior Of Pfas Associated With Afff In the Subsurfacementioning
confidence: 99%